Light-harvesting like domain of the cyanobacterial ferrochelatase - Pazderník, Marek (Jihočeská univerzita, 2020)
This thesis is focused on elucidating the function of the C-terminal transmembrane lightharvesting complex like (LHC) domain of the cyanobacterial ferrochelatase (FeCh). Using the model cyanobacterium Synechocystis PCC 6803, I show that the FeCh LHC domain can bind chlorophyll (Chl) and carotenoids; however, this pigment binding occurs only when the biosynthesis of heme and Chl in the cell is misbalanced. Further, I found that point mutation, which prevents the pigment binding to FeCh LHC domain results in a misregulated ratio between heme and Chl during stress conditions due to low heme accumulation. My data also show that the FeCh LHC domain interacts with CurT protein most likely to localize the FeCh into a specialized membrane domain, where the synthesis of photosystem II is proposed to occur. Based on my data I propose that the role of the FeCh LHC domain is to monitor the availability of Chl during photosystem biogenesis and to coordinate Chl availability with the synthesis of heme.
Light-harvesting like domain of the cyanobacterial ferrochelatase
Keywords: ferrochelatase; light-harvesting complex; heme; chlorophyll; tetrapyrrole pathway; ferrochelatase; light-harvesting complex; heme; chlorophyll; tetrapyrrole pathway